Three case reports of pulmonary mucormycosis with a review of the literature - Zhang, Zhengyang; Wang, Min (Frontiers in Medicine, 2025)
Pulmonary mucormycosis (PM) is an invasive and life-threatening fungal infection that predominantly affects immunocompromised individuals. This study thoroughly examined the disease through three case reports and a literature review. Case 1 involved a patient with type 1 diabetes mellitus diagnosed through bronchoscopic histopathology, who succumbed despite a combination of oral isavuconazole, nebulized amphotericin B, and intravenous amphotericin B cholesteryl sulfate complex. Case 2 involved a patient with follicular non-Hodgkin lymphoma who had a concurrent coronavirus disease 2019 (COVID-19) infection, which was confirmed through metagenomic next-generation sequencing (mNGS) of bronchoalveolar lavage fluid (BALF). The patient experienced clinical improvement following sequential intravenous voriconazole, amphotericin B cholesteryl sulfate complex, and oral isavuconazole. Case 3 involved a patient diagnosed with mNGS in a lung cancer patient with chronic obstructive pulmonary disease, who showed poor therapeutic response to combined intravenous voriconazole, amphotericin B cholesteryl sulfate complex, and oral isavuconazole, resulting in fatal outcomes. Literature synthesis revealed mortality rates of 28.3% with antifungal monotherapy compared to 23.7% when antifungal monotherapy was combined with bronchoscopic intervention; the mortality rate for antifungal–surgical combination therapy was 9%. Notably, all 13 patients receiving multimodal treatment (antifungals, bronchoscopy, and surgery) survived. These findings underscore that combination therapy integrating pharmacotherapy, bronchoscopic intervention, and surgical resection demonstrated significantly superior survival outcomes compared to monotherapy.